The creation of direct photons during interactions of deuterium nuclei at energies of 13.5 GeV and 27.0 GeV - Shapaev Dmitry; Berdnikov Yaroslav (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
In this study, the invariant spectra and nuclear modification factors of direct photons produced in deuteron collisions at energies sqrt{s_{NN}} = 13.5 and 27.0 GeV/nucleon, relevant to the NICA project have been obtained by calculation. In doing this, both nuclear modified parton distribution functions and parton distribution ones found for free nucleons were used. Our analysis indicated that the predicted spectra of direct photons as a function of the transverse momentum, as well as the nuclear modification factors in these interactions were scarcely affected by accounting for the nuclear parton distribution function. It also turned out that the nuclear modification factors for direct photons generated in deuteron collisions at the specified energies depended slightly on the transverse momentum within the range from 1 to 5 GeV, differed from unity, exhibiting values around 0.8.